REAKSI PASAR TERHADAP PENGUMUMAN PENERBITAN SUKUK MUDHARABAH DAN OBLIGASI KONVENSIONAL - Purwaningsih, Purwaningsih; Khoiruddin, Moh. (Management Analysis Journal, 2016)
This research aims to analyse market reaction toward sukuk mudharabah and conventional bonds issue announcement that indicated with abnormal return and trading volume activity. Population in this research is all of sukuk mudharabah and conventional bonds issue announcement registered in IDX period 2012-2015. This research used event study with 21 days of windows period (t-10 to t+10). Samples of this research consist of 5 sukuk mudharabah issue announcements and 65 conventional bonds issue announcements based on purposive sampling method. Analysis methods used in this research are t-test and Paired Samples T-Test. The results of this research show that there are significant abnormal return around the date of sukuk mudharabah issue announcement on t-10, t-8, t-6, and wheres significant abnormal return around the date of conventional bonds issue announcement on t-7, t-3, t-1, t-3, t-4, t-7. In addition, there is no significant difference between trading volume activity before and after to sukuk mudharabah and conventional bonds issue announcement. The market react slow and prolonged so there is not happenedÂ  market efficiency semi-strong form in information and decision. Â